Meningkatkan Pengetahuan Kader Posyandu Dan Posbindu Tentang Skrining Kanker Serviks Melalui Program Pengabdian Masyarakat - Supriyatiningsih; Dianita Sugiyo; Sutantri; Arlina Dewi; Sri Sundari; Wiwik Kusumawati (Abdimas Universal, 2022)
Cervical cancer is the fourth most common cause of cancer death in women worldwide. Many women who come to the health facility for a check-up with cervical cancer are already severe. This happened because of the lack of knowledge of women about the importance of cervical cancer screening. The purpose of this community service is to increase the knowledge of women in Kersan, Bantul regarding cervical cancer screening. The service method implemented was conducting socialization and education to the community regarding the importance of online cervical cancer screening. The participants in this program were 30 Posyandu and Posbindu cadres in Kersan. After this program, many women began to know the importance of getting cervical cancer screening so that they would immediately get treatment.